1998
DOI: 10.1007/bf01246847
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the nitromethane selective quenching rule in micellar anionic sodium dodecylbenzenesulfonate and micellar cationic dodecylethyldimethylammonium bromide solvent media

Abstract: Abstract. Applicability of the nitromethane selective quenching rule for discriminating between alternant versus nonalternant polycyclic aromatic hydrocarbons (PHAs) is examined for 38 representative PAH solutes dissolved in micellar sodium dodecylbenzenesulfonate (SDBS) and in micellar dodecylethyldimethylammonium bromide (DEDAB) solvent media. Experimental results show that nitromethane quenched fluorescence of only the 20 alternant PAHs in the cationic DEDAB surfactant solvent media as expected. Emission in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Reason for that phenomenon is an electronic communication between the pyridinium and the perylene unit. Pyridinium quenches the fluorescence of the perylene through a photo‐induced electron‐transfer (PET) from the excited state of the perylene, that was formed during excitation with light of 408 nm, towards the nitrogen atom of the pyridinium, that has a lowered LUMO energy level compared to that of the perylene [6a,b,d,e, 19] …”
Section: Resultsmentioning
confidence: 99%
“…Reason for that phenomenon is an electronic communication between the pyridinium and the perylene unit. Pyridinium quenches the fluorescence of the perylene through a photo‐induced electron‐transfer (PET) from the excited state of the perylene, that was formed during excitation with light of 408 nm, towards the nitrogen atom of the pyridinium, that has a lowered LUMO energy level compared to that of the perylene [6a,b,d,e, 19] …”
Section: Resultsmentioning
confidence: 99%
“…k q , on the other hand, follows a trend similar to K D and, in the absence of [bmim][BF 4 ], reaches close to diffusion-controlled value. This is expected for favorable quenching of alternant PAHs by nitromethane within aqueous anionic micellar SDS media. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…In order to identify, separate, and detect alternant and nonalternant PAHs, fluorescence spectroscopy offers high sensitivity and selectivity because the quantum yield of most PAHs is quite significant. Zander, Acree, and McGuffin groups have shown that nitromethane selectively quenches the fluorescence of alternant PAHs as opposed to the fluorescence of nonalternant PAHs. In a series of publications, Acree and co-workers using several alternant and nonalternant PAHs have amply established the nitromethane selective quenching rule. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, primary inner filter artifacts can become problematic in the detection of these compounds. Also, nitromethane selective quenching is lost when the PAHs are in the presence of anionic surfactants above their critical micelle concentration (31)(32)(33). It is interesting to note that the selective quenching ability of nitromethane is retained in anionic, carboxylate terminated poly(amido) amine dendrimers, which are referred to as unimolecular micelles (30).…”
mentioning
confidence: 97%